On the use of the adverbs of place ČIA and TEN in the area of Pabradė-Joniškis - Judžentytė, Gintarė (Lietuvių kalba, 2014)
The article deals with one case of the meaning of the adverbs of place čia (‘here’) and ten (‘there’) in the area of Pabradė–Joniškis. The main goal of the article is to demonstrate that in deictic situations, the adverbs čia and ten acquire new meanings. The adverbs of place under consideration are analysed in four different deictic situations: in the case of direct deixis and in imaginary deixis, to be more precise, in its three types. The research has shown that the meanings of čia and ten in deictic situations change and this shift in meaning depends on the direction of the coordinate source (origo) that a subject/agent posits or identifies with. The analysis of dialectal texts in the area of Pabradė–Joniškis has revealed that: 1. Apart from their main meanings of ‘in this place’ and ‘in that place’, based the usage of language in the area under analysis, the adverbs of place čia and ten, when accompanied by a gesture in a deictic situation acquire new meanings. Depending on the direction that the speaker is pointing to, they can mean the right or the left side, whereas if the speaker points directly, these words can obtain the meaning of ‘straight’. a) When the adverbs čia and ten acquire the meanings of ‘right’ and ‘left’, the correlation of distance between them disappears, i.e. with respect to origo they both refer to a place that is further, to the right or to the left. b) When the adverbs čia and ten acquire the meaning of ‘straight’, the distance correlation between them also disappears, i.e. from the point of view of origo they both refer to a place that is straight. 2. The most outstanding is the first type of imaginary deixis in the usage of these adverbs: a) Since the conceptual space is transferred to the space between the interlocutors and they both understand that space as being proximal, in this situation the deictic ten is not used at all, i.e. only cases of the deictic čia are used. b) Only in the first case of imaginary deixis does the deictic čia acquire a very unconventional meaning of distance. When used together with a deictic gesture, apart from the meaning of ‘in this place (between us)’, it could also mean ‘this distance’. 3.The analysis carried out has demonstrated that in the language of Pabradė–Joniškis area the deictic čia and ten acquire the same meanings as in the East Aukštaitian Utena subdialect.